ASSESSMENT OF KNOWLEDGE TOWARD PREVENTION OF HEPATITIS B INFECTION AND VACCINATION STATUS AMONG HEALTH CARE WORKERS AT A TERTIARY CARE CENTRE IN EASTERN INDIA - SUBHA SANKHA KUNDU; MOUMITA KUNDU; MUKESH KUMAR; DHAVAL PAREKH; ANAND KISHORE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present study aims to assess the knowledge about Hepatitis B infection of healthcare workers (HCWs) and their vaccination status. Methods: This was a cross-sectional descriptive study, carried out over a period of 4 months, at a tertiary care hospital in Eastern India. The study enrolled 151 HCWs, including nurses and paramedical staff employed on either a permanent or contractual basis. Participants were selected randomly, and data were obtained using a structured, pre-tested data collection tool. The questionnaire included sections to capture sociodemographic details, assess knowledge about Hepatitis B virus (HBV) infection, determine vaccination status, and identify reasons for partial or lack of vaccination. Results: Among the 151 participants, 29.8% were nurses, and 70.2% were auxiliary health workers, including laboratory technicians, administrative staff, housekeeping staff, ward attendants, and ambulance drivers. While all nurses exhibited complete knowledge across all domains of HBV awareness, only 14% of auxiliary health workers knew the causative organism and 9% were aware of prevention strategies. Vaccination coverage was suboptimal, with 48.3% fully vaccinated, 30.5% partially vaccinated, and 21.2% unvaccinated. Unvaccinated participants cited a lack of awareness (62.5%) and perceived irrelevance (31.3%) as major barriers. Among partially vaccinated participants, 65.2% were unaware of their vaccination schedule. Conclusion: Significant gaps in HBV-related knowledge and vaccination coverage persist among auxiliary health workers, highlighting the need for targeted educational programs and routine workplace vaccination initiatives. Enhancing awareness about vaccination schedules and ensuring easy access to vaccines are critical steps to mitigate HBV transmission risks in healthcare settings and protect HCWs.